복강 내 미주신경에 발생한 퇴행성 신경초종의 복강경하 절제술 - 안혜성(Hye Seong Ahn); 박도중(Do Joong Park); 이혜승(Hye Seung Lee); 이혁준(Hyuk-Joon Lee); 김형호(Hyung-Ho Kim); 양한광(Han-Kwang Yang) (Annals of surgical treatment and research, 2006)
Schwannomas are benign schwann cell tumors arising from peripheral nerves or spinal roots. Most schwannomas occur in the cephalocervical region and limbs with a few cases occurring in the intraabdominal space especially in the lesser sac. Among them. ancient schwannomas are benign schwannomas with degenerative changes such as cyst formation, calcification, hemorrhage and hyalinizaion. Histologically ancient schwannomas show degenerative changes with marked nuclear atypia and both cinical and radiologic features specific to schwannoma are usually absent. So it is difficult to diagnose ancient schwannoma preoperatively and distinguish it from malignant tumors. We describe herein a very rare case of benign ancient schwannoma of vagus nerve in the lesser omentum. A 31-year-old male patient underwent laparosocpic resection and discharged on the second postoperative day without any complications. Laparoscopic surgical technique is safe and feasible for the diagnosis and treatment of benign solid tumors in the lesser omentum such as schwannoma. (J Korean Surg Soc 2006;71:464-468) KCI Citation Count: 0